(untitled) (UNIZIK Journal of STM Education, 2025)
Digital divide remains a significant challenge in ensuring equal access to ethical and values in education. It significantly impacts in the teaching and learning of science, especially in developing regions like Nigeria. This divide hampers access to quality education, affecting both students and educators, addressing this issue is crucial for sustainable national development. As technology continues to revolutionize education, disparities in digital access create inequalities in the moral development of individuals, which in turn affects national growth and stability. This paper examines the implications of the digital divide on the provision of ethics and values education. It advocates for re-engineering of national strategies to bridge this gap and foster inclusive, sustainable development. By leveraging technology equitably and responsibly, nations can empower citizens with the moral compass necessary to navigate modern challenges and contribute meaningfully to national growth